El-Thoria Art Exhibition: An Experiential Learning-Based Model For Developing 21st-Century Skills In Islamic Boarding Schools - Haliza Nur Azkia; Roshida Yulia Rindang; Cecep Sobar Rochmat; Ahmad Saifullah (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
The development of twenty-first-century skills has become a major priority in education, requiring learning approaches that integrate critical thinking, creativity, communication, and collaboration (4Cs). Within Islamic boarding schools (pesantren), these competencies need to be developed while preserving Islamic educational values. This study aimed to describe the implementation of the El-Thoria Art Exhibition based on Experiential Learning, examine its contribution to the development of santri's 21st-century skills, and identify the Islamic values reflected throughout the program. A descriptive qualitative field study was conducted at Pondok Modern Darussalam Gontor Putri Campus 1 involving 29 purposively selected informants. Data were collected through observation, in-depth interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the El-Thoria Art Exhibition was implemented through the stages of Kolb's Experiential Learning cycle, providing authentic learning experiences in planning, artwork production, exhibition management, presentation, and reflection. These activities illustrated the development of critical thinking through collaborative problem-solving and decision-making, creativity through artwork design and innovation, communication through presentations and interactions with visitors, and collaboration through teamwork and shared responsibilities. The findings also revealed the internalization of Islamic values, including amanah (trustworthiness), responsibility, discipline, ta'awun (mutual cooperation), and leadership during the exhibition process. These findings suggest that the El-Thoria Art Exhibition represents an experiential learning practice that integrates the development of 21st-century skills with Islamic character education within the context of pesantren.